THE USE OF SOCIAL MEDIA IN DEVELOPING CULINARY MSMEs IN BANDAR SELAMAT VILLAGE, MEDAN TEMBUNG DISTRICT - Parlindungan Lubis (Program Pascasarjana UIN Sumatera Utara, 2025)
Digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt social media as a communication and marketing strategy. However, the use of social media by MSMEs, particularly in semi-urban areas such as Bandar Selamat Village, still faces various challenges. This study aims to analyze the role of social media in improving the performance of culinary MSMEs, by highlighting its impact on customer growth, increased sales, and business development. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews with six MSMEs, and documentation of their digital business activities. The results show that active and strategic use of social media has a positive impact on business performance, especially in aspects of customer interaction and brand presence. These findings support digital marketing communication theory and strengthen empirical evidence regarding the importance of digital literacy in MSME development. This study also reveals variations in effectiveness among business actors influenced by digital skills and content strategies. Implications of this study include the need for social media training for MSMEs and support for an inclusive digital ecosystem. Further research is recommended to cover a wider range of regions and business sectors to gain a more comprehensive understanding.